Didactic strategies and the learning styles in an English class as a second language (esl class) - Meza, Orley Benedicto Reyes; Andrade Torres, María Victoria; Rosales, Francisca Margarita Avila; Moreira Mejía, Luis Leonardo (International Journal of Psychosocial Rehabilitation, 2020)
The objective of the work is to analyze the learning styles that are put into practice by the students and their relevance during the process of teaching English as a second language. In the Raymundo Aveiga Educational Unit of the municipality of Chone, province of Manabí, Ecuador, difficulties have been confronted with the learning of English, estimating that more than a methodological problem, they may be given in the methodological relationship between the learning styles that they put into practice the students and the teaching strategies applied by the teachers. The research is of a qualitative type, with a multimethodical, interpretive and naturalistic approach, aiming to make an approach to the problems derived from the application by the students of the learning styles of English as a second language and the imprint of the appropriate teaching strategies in each case attending to the natural environment. The biographical-narrative method was used to produce an approach to the world of the personal meanings of each student. A narrative perspective was adopted as a way of constructing reality using interview and real-time observation of a class with didactic planning, where the four learning styles were revealed. A bibliographic review was carried out in order to delve into the topic related to didactic strategies and learning styles, for which the Desh Research research method was applied. The basic techniques applied correspond to observation, interviews and surveys, for which the Honey & Alonzo questionnaire for Learning Styles CHAEA was used. The work tries to demonstrate that the learning styles and the didactic strategies in an ESL class are the result of a dynamic that develops abilities and skills in English taking into account the individual differences of the students.